2001
DOI: 10.1073/pnas.191380698
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral screening for cocaine sensitivity in mutagenized zebrafish

Abstract: Understanding the molecular basis of addiction could be greatly aided by using forward genetic manipulation to lengthen the list of candidate genes involved in this complex process. Here, we report that zebrafish exhibit cocaine-induced conditioned place preference. In a pilot screen of 18 F2 generation families of mutagenized fish, we found three with abnormally low responses to cocaine. This behavior was inherited by the F3 generation in a manner that suggests the abnormalities were because of dominant mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
266
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(285 citation statements)
references
References 24 publications
8
266
1
2
Order By: Relevance
“…The use of adult zebrafish as a model system to study drug addiction has shown exceptional promise (Darland and Dowling, 2001). However, there is a major gap in our understanding of the developmental consequences of embryonic nicotine exposure.…”
Section: Consequences Of Nicotine Exposure On Morphology and Behaviormentioning
confidence: 99%
“…The use of adult zebrafish as a model system to study drug addiction has shown exceptional promise (Darland and Dowling, 2001). However, there is a major gap in our understanding of the developmental consequences of embryonic nicotine exposure.…”
Section: Consequences Of Nicotine Exposure On Morphology and Behaviormentioning
confidence: 99%
“…Namely, zebrafish can learn (Darland and Dowling, 2001;Sison and Gerlai, 2010) and are amenable to neurodevelopmental and neurogenetic analysis and manipulation (Asakawa et al, 2008;Baier and Scott, 2009). Even in an early stage of development zebrafish larvae possess a wide spectrum of innate and experience-dependent behaviors (Burgess and Granato, 2007;Gerlach et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The role of dopaminergic signaling in the zebrafish visual system has been investigated using behavioral and electrophysiological methods (Li and Dowling, 2000;Maaswinkel and Li, 2003), and mutants have been identified in the regulatory pathways controlling the development of catecholaminergic neurons (Guo et al, 1999. In addition, zebrafish have a large repertoire of behaviors, some of which (e.g., locomotor activity, conditioned place preference, addictive behavior, and visual thresholds) can be associated with dopaminergic signaling (Gerlai et al, 2000;Darland and Dowling, 2001;Neuhauss, 2003).…”
Section: Introductionmentioning
confidence: 99%